Military Tribunate in the Careers of Roman Senators of the Severan Period. Part I: Introductory Issues - Okoń, Danuta (Polskie Towarzystwo Filologiczne, 2019)
During the 42 years of the rule of the Severan dynasty (193–235), several thousand people with the title of military tribune probably served in troops of the Roman Empire. Some of them then entered the Roman Senate, starting a public career (often a long-term career) and forming the core of the State government. The aim of this paper is to answer the following questions: What were the terms used in the inscriptions for military tribunate? How were tribunes appointed and how long did they hold their offices? How many military tribunes were there in the Severan Period? How many of them are currently known and what territorial and social circles didthey come from?
Keywords: military; Rome